(untitled) (Research, Society and Development, 2021)
Railway bridges are key elements in the world transport landscape, presenting a variety of possible applications. However, it is necessary to check the performance of its structure in order to prevent damage in terms of design, because if the project is applied without there being a verification of its structure and its components, undesirable accidents may occur. The essential parameters to be investigated are the equivalent carbon content of the steel (CEq), the Preheating Temperature (TPA), the Net Welding Energy (Hl) and the welding process itself, since they influence the mechanical properties of the material. This the article addresses the determination of welding parameters for a railway bridge, which are obtained from the chemical composition of the structural steel of the bridge. It also determines issues of dimensioning, tonnage and the choice of the ideal welding process for a project of great magnitude, exemplifying technical procedures inherent to the construction.